THE EVENT OF BREAST ENGORGEMENT ON MOTHERS WHO ARE UNDERGOING AND NOT UNDERGOING THE MATERNITY BLUES - nunuk nur hayati; partina - - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Pregnancy and giving a birth are natural processes experienced by productive ages women; in this case the mothers will undergo several changes, either physically or psychologically. After giving a birth, some adjustments are required by mothers. Some of them are able to adjust themselves and some of them are not. Events, Reviews those Unable to adjust Themselves undergo a psychological disturbance the so-called "Maternity Blues". The mother's milk clogging is one of the problems during the period of parturition. This matter can not be neglected, because the best food for the babies is the Mother's Milk. This is a cross-sectional research. The researcher performed a research on mothers having postpartum on the 2nd day till the 10th day, the for the undergoing and non-undergoing the Maternity Blues. The samples consist of 36 mothers of having postpartum with the inclusion criteria, among others: the mother with postpartum on the 2nd till the 10th day, understanding the English language, having the history of depression, having the Apgar Score of more than 7, the baby is full term (having enough month in its mother's womb). Instruments used in this research are the Maternity Blues Scale, functioning to detect Whether a mother Suffering from Maternity Blues or not, and the other instrument to know the existence of the Mother's Milk clogging is the Six-Point engorgement Sale. The Data are analysed by using the Man Witney Test. Based on the hypothetical testing, it is Obtained that the value of p = 0.930 bigger than 0:05. Thus, it is concluded that H a is rejected, meaning that there is no difference in the events of the Mother's Milk on mothers undergoing clogging and non-undergoing the Maternity Blues. The research output indicates that there is no difference in the events of the Mother's Milk on mothers undergoing clogging and non-undergoing the Maternity Blues, in the which both of them similarly experience the Mother's Milk clogging.